Comparison of bovine transfer factor and Micotil®: effects on health and performance of receiving heifers - Sean P. Montgomery; M.A. Greenquist; J.J. Sindt; W.F. Miller; J.N. Pike; E.J. Good; E.R. Loe; M.J. Sulpizio; T.J. Kessen; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2004)
Transfer factors are antigen-specific products of T lymphocytes that are capable of transferring delayed-type hypersensitivity and cell-mediated immunity. We evaluated bovine transfer factor (TF) for use in receiving cattle. Crossbred beef heifers (n = 665) initially weighing 495 lb were used to determine the effects of TF on the health and performance of beef cattle during a 36-day receiving period. Heifers were processed within 24 hours after arrival. Treatments were subcutaneous injection with 1.5 ml of Micotil®/100 lb of body weight or oral administration of 700 mg of TF isolated from bovine colostrum. Heifers given TF during initial processing received an additional 700 mg/day of TF in the diet on days 2 through 5. The percentage of heifers treated at least one, two, or three times for bovine respiratory disease (BRD) was greater (P<0.01) for heifers given TF than for heifers given Micotil (72.5 vs. 47.1; 31.5 vs. 14.7; and 18.0 vs. 4.2, respectively). There were no differences between TF and Micotil with respect to dry matter intake, weight gain, or gain efficiency of heifers. Subsequent in vitro fermentations indicated that TF protein is readily degraded by ruminal microbes. Oral administration of TF was not as effective as Micotil injection in decreasing BRD in receiving cattle.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Micotil®; Bovine transfer factor